Influência da desnutrição energético-protéica no processo de translocação bacteriana em modelo experimental de obstrução intestinal em ratos - Maria Augusta Gomes Pereira (2005)
Malnutrition, highly prevalent in developing countries, is an old suffering that afflicts the humanity. The protein-energy malnutrition is presented as a state of food deficiency, with deficit in proteins and calories, provoking lower supplying of nutrients to the cells. Some studies have shown evidences of interaction between malnutrition and bacterial translocation. Bacterial translocation is a process in which microorganisms from gutnormal microbiota cross the intestinal mucosa in order to reach other organs. This can occur due to three situations: dysfunction of the intestinal mucosal barrier, alterationof intestinal microbiota and host immune deficiency. In our study, the distal ileum was ligated for induction of the intestinal obstruction in rats. Protein-energy food restrictionimposed throughout the experiment had the aim of evaluating the influence of malnutrition on intestinal translocation in the animals. Control group animals fed diet ad libitum and the malnourished rats fed 65% of the amount consumed by the control group. In order to control for surgical stress, wellnourished and malnourished rats were Sham operated. Wellnourished and malnourished animals were submitted to ileum ligation. All animals were inoculated in the ileum with 99mTc-E.coli (108 CFU). The animals were sacrificed 24 hours after 99mTc-E.coli inoculation, blood sample was collected and some organs removed (mesenteric lymphonodes, liver, spleen, and lungs) for verification of thebacterial translocation. The bacterial translocation was evaluated by the determination of the radioactivity in the organs and blood. The results showed that in the animals submitted to the intestinal ligation, bacterial translocation was significantly higher (p 0,05) than in Sham operated animals. Animals submitted to the intestinal obstruction and Sham operated wellnourished animals, compared to the malnourished ones, did not show significant differences in bacterial translocation to the organs and blood (p>0,05). Therefore, the obtained data suggest that protein-energy-malnutrition imposed to the rats did not interfere with the process of bacterial translocation in the experimental model of ileum ligation in order to obtain intestinal obstruction